2019
DOI: 10.1007/978-3-030-34992-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous t-Resilient Consensus in Arbitrary Graphs

Abstract: We study the number of rounds needed to solve consensus in a synchronous network G where at most t nodes may fail by crashing. This problem has been thoroughly studied when G is a complete graph, but very little is known when G is arbitrary. We define a notion of radius(G, t), that extends the standard graph theoretical notion of radius, for considering all the ways in which t nodes may crash, and we present an algorithm that solves consensus in radius(G, t) rounds. Then we derive a lower bound showing that, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Many technical interesting issues arise, such as defining morphisms between complexes, understanding the relation between belief and a dead agent, but the main point is that our work opens the way to give a formal epistemic semantics to distributed systems where processes may fail and failures are detectable (as in the synchronous crash failure model). It would be interesting to use our simplicial model to reason about the solvability of tasks in such systems, for example, the following have not been studied using epistemic logic, to the best of our knowledge: non-complete communication (instead of broadcast situation we considered here) graphs [4], renaming [28], and lattice agreement [36].…”
Section: Discussionmentioning
confidence: 99%
“…Many technical interesting issues arise, such as defining morphisms between complexes, understanding the relation between belief and a dead agent, but the main point is that our work opens the way to give a formal epistemic semantics to distributed systems where processes may fail and failures are detectable (as in the synchronous crash failure model). It would be interesting to use our simplicial model to reason about the solvability of tasks in such systems, for example, the following have not been studied using epistemic logic, to the best of our knowledge: non-complete communication (instead of broadcast situation we considered here) graphs [4], renaming [28], and lattice agreement [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a related work, Choudhury et al [18] provided a time-optimal algorithm to solve Consensus in directed graphs with node crashes. Castañeda et al [8] considered networks with nodes prone to crashes with an upper bound t on the number of crashes and showed that, as long at the network remained (t + 1)-connected, Consensus was solvable in a number of rounds determined by how conducive the network was to broadcasting. Chlebus et al [15] studied networks with Byzantine nodes such that the removal of faulty nodes leaves a network that is sufficiently connected; they gave fast solutions to Consensus and showed a separation of Consensus with Byzantine nodes from Consensus with Byzantine nodes using message authentication, with respect to asymptotic time performance in suitably connected networks.…”
Section: Introductionmentioning
confidence: 99%